The RaPID-Ω system: Room and proctor intelligent decider for large scale tests programming - Morales, Fernando (Yugoslav Journal of Operations Research, 2021)
We present the documentation and mathematical modeling of the open-box system RaPID/?. The software is designed for the choice of classrooms and the assignment of proctoring duties in massive tests, which is a common situation in educational institutions offering large coordinated lower division courses. The mathematical model is a binary integer programming problem: a combination of the 0-1 knapsack problem and the job-assignment problem. The system makes decisions according to the following criteria in order of priority: minimization of labor-hours, maximization of equity in the distribution of duties and maximization of the proctoring quality.